Fishery in the Pendjari River (Benin): ﬁ shermen, regulations and conﬂ icts - Moritz, Timo; LALEYE, PHILIPPE A. (My University, 2017)
The Pendjari river harbours a diverse and productive ichthyofauna. Conﬂ icts of utilizing these ﬁ sh stocks may arise for several reasons: the river forms over 150 km the border of Benin and Burkina Faso; it ﬂ ows through areas with different states of protection; and ﬁ shery is performed by locals and non-locals in various intensities for money-generation or only for subsistence. Questionnaires were conducted between October and November 2006 on the Benin side of the Pendjari River including 40 ﬁ shermen and 46 occa-sionally ﬁ shing persons from six villages. Furthermore eight long-distance traders and four local ﬁ sh sellers have been interviewed, as well as ten persons related to the park management. Three groups of ﬁ shermen can be distinguished: professionals (68% non-natives), semi-professionals (61% non-natives) ﬁ shing only during the dry season, and occasional ﬁ shermen. Within the Pendjari National Park several special regulations apply and fees have to be paid for the use of professional ﬁ shing equipment. Violation of park regulations occurs regularly. About 80% of the catch from the Pendjari River is sold to traders. Proﬁ t is mainly generated by non-locals. To ensure a future sustainable utilisation of the Pendjari ﬁ sh stocks by locals and to ensure, at the same time, the conservation of the aquatic diversity in the Pendjari region, a set of measurements is proposed: more stringent application of existing regulations and laws, establishment of bi-national agreements on regulations, strengthening of local ﬁ shermen, and creation of a local ﬁ shermen organization Fishery in the Pendjari River (Benin): fishermen, regulations and conflicts (PDF Download Available). Available from: https://www.researchgate.net/publication/315768675_Fishery_in_the_Pendjari_River_Benin_fishermen_regulations_and_conflicts [accessed Feb 27 2018].
Keywords: Africa; freshwater; protected areas; Pendjari National Park; Volta basin